ANALISIS YURIDIS KEWENANGAN PEMERIKSAAN KENDARAAN BERMOTOR DI JALAN OLEH PPNS DI BIDANG LALU LINTAS DAN ANGKUTAN JALAN - Jaya, Herry Shan; Syahrin, Alvi; Yunara, Edi; Leviza, Jelly (Universitas Dharmawangsa, 2023)
Crime is a common problem in society and can be committed by anyone, both the perpetrator and the victim. Criminal policy used in tackling crime in Indonesia consists of two methods, namely preventive and repressive. In its implementation, it involves crime prevention investigators, police investigators, and civil servants (PPNS). However, the problem is the overlap between police investigators and PPNS because both have different authorities in conducting investigations. One of the well-known PPNS in Indonesia is the Road Traffic and Transport PPNS. In handling traffic and transport criminal offences, the investigation is carried out by two investigation agencies in accordance with Article 259 paragraph 1 of Law 22/2009 on traffic and transport. In the implementation of crime policy, it is important to coordinate activities between police and PPNS investigators to avoid overlapping authority. The role of the community in preventing crime by reporting suspicious activities to the authorities is also very important. In this way, it is hoped that the public can prevent crime by reporting suspicious activities to the authorities.